Molecular surveillance and phylogenetic analysis of Theileria annulata in bovine at Baghdad city/ Iraq - Kawan, May Hameed (The Iraqi Journal of Veterinary Medicine, 2019)
This study is conducted to investigate Theileria spp. by traditional and molecular methods. A total of 150 blood and 50 lymph samples were collected from local breed symptomatically and asymptomatically cattle of both sexes with age ranging from less than 6 months to more than 1 year during the four seasons of 2018, in different parts at Baghdad city / Iraq. Microscopic examination of Giemsa stained blood smears revealed 39.33 %( 59/150) rate of infection with bovine theileriosis and 34 %( 17/50) positive lymph smears. Statistically no significant difference recorded between female and male: 42.04 % (37/88) and 35.48 % (22/62) respectively. Higher rate of infection 57.97 % (40/69) were recorded in more than 1 year age and 0 % in less than 6 months. 48.93 % (23/47) rate of bovine theileriosis was recorded during summer and 39.53 % (17/43) ; 37.5 % (15/40) rates were recorded during spring and autumn respectively, while the lower rate recorded in winter 20 % (4/20). DNA extraction and polymerase chain reaction (conventional PCR) were done on all cattle blood samples the result recorded that 22 out of 25 samples were positive for Theileria spp and Theileria annulata with percentage of 88 %. Also DNA sequencing analysis and genetic relationship were conducted by phylogenetic analysis.